Celtic Literature - Arnold, Matthew, 1822-1888 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Study of Celtic Literature" by Matthew Arnold is a collection of lectures on the understanding and appreciation of Celtic literary heritage, likely written in the late 19th century. The text serves as an exploration of Celtic literature's richness and complexity, addressing how these works can resonate with broader cultural and literary discussions. Arnold aims to highlight the importance of understanding the Celtic perspective and contributions to literature, emphasizing their cultural significance despite challenges they face from dominant narratives. At the start of the book, Arnold discusses his experiences and reflections during visits to Wales, particularly participating in an Eisteddfod$1 (Ban assembly of Welsh bards and poets. He reflects on the contrasting Celtic landscape and culture with the encroaching Saxon influence, expressing a deep admiration for the poetic traditions and historical roots of the Celtic peoples. Arnold's introduction sets the stage for a critical yet appreciative examination of Celtic literary works, steering the reader towards an understanding of their importance not only within the context of Wales or Ireland but also regarding their contributions to a shared literary heritage. (This is an automatically generated summary.)s
Release date is 2004-02-01
Transcribed from the 1891 Smith, Elder and Co. edition by David Price
Keywords: Celtic literature -- History and criticism